Pengaruh Elektroakupunktur Titik Zusanli (ST 36) dan Sanyinjiao (SP6) terhadap Ketebalan Korteks Adrenal Tikus (Rattus norvegicus) yang Dipapar Bising Intermiten - Luthfiyanto, Muhammad; Muthmainah, .; Handayani, Selfi (Nexus Biomedika, 2014)
Background: Noise exposure triggers stress and thickens adrenal cortex. Electroacupuncture on Zusanli (ST 36) and Sanyinjiao (SP 6) acupoints is known to reduce stress and improve the hypothalamic-pituitary-adrenal (HPA) axis. This study aimed to know the effect of electroacupuncture (EA) at Zusanli (ST 36) and Sanyinjiao (SP 6) acupoints towards adrenal cortex thickness of rats (Rattus norvegicus) exposed by intermittent noise. Methods: This study was a laboratory experimental study with the post-test only control group design. The subject of this study was male Wistar rats (Rattus norvegicus), 1-2 months old, and 200-250 grams of body weight. Twenty seven rats were taken by consecutive sampling. The rats were divided into 3 groups randomly, each group consisted of 9 rats. The Control Group (KK) was untreated, the treatment group 1 (KP1) was exposed by the noise, the treatment group 2 (KP2) was exposed by the noise and treated with electroacupuncture. Noise exposure was conducted for about 8 hours/day intermittently during 21 days respectively, while electroacupuncture treatment was done every 3 days, so there were 7 times of electroacupuncture treatment. Electroacupuncture was conducted at Zusanli (ST 36) and Sanyinjiao (SP 6) acupoints at 2 Hz of frequency in a continuous wave for 15 minutes that its intensity was adjusted until local muscle contractions were seen. Â On the 22nd day, rats were sacrificed by neck dislocation and ratâs adrenal glands were taken and stained with Hematoxylin-Eosin for histological study. The thickness of ratâs adrenal cortex was observed under light microscope with 400x magnification. The data were analyzed by One Way ANOVA test and LSD test (Î± = 0.05). Results: The average of cortex adrenal thickness in KK, Â KP1 and KP2 were 454.93 Â± 2.03 Âµm, 565.59 Â± 0.97 Âµm and 479.65 Â± 1.34 Âµm, consecutively. One Way ANOVA test showed significant differences among the three groups with p=0.000 (p<0.05). LSD test also showed significant differences between KK-KP1, KK-KP2, KP1-KP2 with each of p=0.000 (p<0.05). Conclusion: Electroacupuncture at Zusanli (ST 36) and Sanyinjiao (SP 6) acupoints affected to prevent the thickening of adrenal cortex of rats (Rattus norvegicus) exposed by intermittent noise. Keywords: electroacupuncture, Zusanli (ST 36), Sanyinjiao (SP 6), noise, adrenal cortexâs thickness.Â